Educational actions for the elderly - Rejane Millions Viana Meneses; Rafael Tavares Silveira Silva; Rafaela Fernandes de Carvalho; Ana Paula de Oliveira Bezerra Souza Santos; Jamilly Arita Veras de Almeida; Angélica Teresa Nascimento de Medeiros (Rev Rene)
In the aging process, the older adults are faced with the emergence of chronic diseases that often reflect in difficulties for health maintenance. Therefore, it is important to work with seniors to promote the improvement in lifestyle. This article is a report from a research project at the Federal University of Rio Grande do Norte, which carries out educational actions in the Inaraí Association (Natal,RN,Brazil), with the objective of divulging activities and thereby stimulate the formation of groups that aim at promoting the health of the elderly. To develop the actions, we rely on the information in the epidemiological profile previously developed in the Association, from then on, through weekly meetings collected with elderly women. We intend to stimulate good habits of life, in order to make possible the improvement of lifestyle and, therefore, to promote health for the group.